Factors Affecting Students on Enrollment in Higher Educational Institutions (HEIs) - K.C., Sudarshan; Maharjan, Babita; Maharjan, Reena (Shahid Kirti Multidisciplinary Journal, 2024)
Community colleges are vital to the higher education system in Nepal. A Community college can act as a medium of globalization in today’s competitive world. The community college can be a great asset for local community to contribute higher education at local level. It has greater contribution to empower the weaker sections of the society through higher education. But the choice of students towards these higher educational institutions is not satisfactory. Majority of the students staying at Kirtipur enroll in colleges specially located in Kathmandu Metropolitan City and Lalitpur Metropolitan City. So, the purpose of this study is to identify the major factors which are attracting students to enroll in private colleges outside Kirtipur. The study was conducted among 133 students staying in Kirtipur but studying outside Kirtipur Municipality. The result of the study shows academic programs, college fees, educational facilities, quality education and promotion have positive effect on students’ enrollment, location and social factors have no effect on it.